Fault resilient FPGA design for 28 nm ZYNQ system-on-chip based radiation monitoring system at CERN. (September 2019) - Toner, C.; Boukabache, H.; Ducos, G.; Pangallo, M.; Danzeca, S.; Widorski, M.; Roesler, S.; Perrin, D.
Abstract: CERN's new generation of radiation monitoring devices for radiation protection, CROME (CERN RadiatiOn Monitoring Electronics) uses a fully reconfigurable 28 nm Xilinx Zynq SoC (System on Chip) for high-end embedded calculations, communication and data storage. In order to meet stringent safety requirements applicable for radiation protection instrumentation, CROME uses the FPGA section of the SoC for all safety critical functions. Whereas the SoC's dual core ARM processor is running an embedded operating system which is used both for communication with the CERN supervisory system and for data management. Due to the use of an embedded Linux OS without a virtualisation layer, the functional reliability of the SoC's FPGA section is considered much greater than the ARM processing system which can be subject to software crashes due to data corruption. This assumption had a central role in CROME's calculation architecture. In order to confirm the assumption and therefore the reliability and robustness of our design, random faults have been voluntarily induced in the SoC by exposing it to ionising radiation of sufficient energy in the CHARM facility, creating Single Event Upsets (SEU). CROME is the first known radiation monitoring system using the FPGA section of a SoC in a safety application. This paper presents the characterisation results of the system in the CHARM facility during a testing campaign of 6 months under an average dose rate of ≥0.1 Gy/day. The tests have provided valuable information on the suitability of this architecture for similar applications. Highlights: It has been confirmed that it is possible to use an Xilinx Zynq SoC for ionising radiation monitoring equipment With the adequate hardening mechanism, we have proven that a crash of the Linux operating system doesn't interfere in any way with the safety critical functions implemented into the FPGA Under mixed radiation fields, we have observed into the Xilinx Zynq SoC 7020: 117 more crashes of the PS than the PL